Methods of early diagnosis and pharmacological prevention of pancreatitis after endoscopic papillosphincterotomy - T. R. Spiridonov; E. D. Novikova; T. O. El'cov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. The most frequent complication of endoscopic papillosphincterotomy (EPST) is acute pancreatitis. This complication is supposed to be based on mechanical, chemical, hydrostatic, enzymatic and thermal impact on pancreatic ducts and parenchyma. According to different literature data, the incidence of post-EPST pancreatitis (PEP) varies from 30 to 40 %, and the mortality rate is 2–10 %.The aim of the investigation was to expand information about peculiarities of early diagnostics and prevention of post-EST pancreatitis at the present stage.Materials and methods. To reach the set goal we analyzed 559 case histories of patients with diagnosed cholelithiasis, 319 of them underwent EPST.Results. During the study it was found out, that elevated neutrophils/lymphocytes ratio over 4,96 (p = 0,001), high LDH level over 250 IU/ml (p = 0,01), as well as Creactive to albumin index over 0,180 (p = 0,001) are reliable markers of early diagnosis. Also, indirect diagnostic markers of PEEP are biochemical signs of cholestasis and cytolysis of hepatocytes, as well as hyperglycemia combined with glucosuria. We consider the inclusion of intraoperative injections of papillotomy wound margins with Epinephrine in combination with subsequent Somatostatin administration in combination with rectal Diclofenac and intravenous hydration with Reamberin to be the most effective strategy for PEP prevention.Conclusions. Thus, we can conclude that despite the ongoing research and the search for effective algorithms for the prevention and early diagnosis of PEP, their data often contradict each other or simply do not confirm their effectiveness. The problem of prevention and diagnosis of PEP remains complex and requires further study. There are discrepancies, sometimes significant ones, in the current literature, which provides grounds for the development and research of new methods of early diagnosis and prevention.